Optimal Postoperative Treatment for Composite Laryngeal Small Cell Carcinoma. (15th September 2013) - Ebisumoto, Koji; Sakai, Akihiro; Okami, Kenji; Sugimoto, Ryousuke; Saito, Kosuke; Iida, Masahiro
Abstract : Small cell carcinoma (SmCC) most commonly occurs in the lung and rarely arises from the head and neck region. Further, composite SmCC is extremely rare. Therefore, no postoperative treatment strategy has been established. We report a 59-year-old male patient referred to our outpatient clinic for further examination and treatment of a laryngeal tumor. Biopsy from the tumor revealed squamous cell carcinoma (SCC). The preoperative diagnosis was supraglottic SCC (T3N2bM0), and total laryngectomy and bilateral neck dissection were performed. Pathological examination revealed 2 individual cancer components: SmCC and SCC. Postoperative chemoradiotherapy (2 courses of cisplatin (CDDP) and etoposide (VP-16)) was indicated. Following the postoperative chemoradiotherapy, 2 courses of adjuvant chemotherapy were administered. The patient is currently alive with no evidence of disease at 36 months following the completion of therapy. Postoperative chemoradiotherapy and adjuvant chemotherapy are optimal treatment strategies for laryngeal composite SmCC.